Size Effect of Blended Learning Model on Students' Problem Solving Ability in Geography Learning - Santi Mareta; Ilwandri Ilwandri; Tomi Apra Santosa (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the effect size of the blended learning model on students' problem-solving in geography learning. This research is meta-analysis research. The data sources in this study came from 11 national and international journals. The data source search process comes from Google Scholar, ScienceDirect, and Eric. Data collection techniques are direct observation and documentation through online databases. Data analysis is a quantitative descriptive statistical analysis technique with the help of the JSAP application. The results of this study show the average value of Effect Size (ES = 0.872) high criteria. This finding explains the significant effect of the blended learning model on students’ problem-solving ability in geography learning. Furthermore, the blended learning model can be done online and offline so as to create a more effective and efficient learning atmosphere without time limits.